Effect of Preoperative Hormonal Therapy in Hypospadias Surgery: Evaluation of the current practice at the Pediatric surgery Clinic, Clinical Center University of Sarajevo - Jonuzi, Asmir; Zvizdic, Zlatan; Popovic, Nusret; Milisic, Emir; Begic, Edin; Kulovac, Benjamin (Iranian Journal of Pediatric Surgery, 2019)
Introduction:The most common congenital abnormality of the penis is hypospadias. Although the main treatment is surgical; hormone therapy with dihydrotestosterone is also used. Materials and Methods: This randomized clinical trial was carried out between January 2012 and December 2017 on 79 children with hypospadias (in the Clinic of Pediatric Surgery, Clinical Centre University of Sarajevo). Their mean age was 38.2±2.8 months. GroupI included 36 children whom were treated with 2.5% dihydrotestosterone gel which was applied twice a day to the penile shaft and glans for one month prior to surgery. GroupII included 43 children whom did not receive any treatment preoperatively. Results: Mean age of patients in group I was 37.3±6.3 months and in group II it was 39.1±5.9 months which were comparable. Complications occurring postoperatively were: urethrocutaneous fistula in 6 patients (13.9%) in group II, versus 1 patient (2.7%) in group I. There were 2 patients with meatalstenosis in group II (4.7%), and 3 (8.3%) in group I. Finally, there was a significant difference (p<0.05) between the overall reoperation rates between groups (p<0.05). Conclusion: Pretreatment with 2.5% dihydrotestosterone transdermal gel before hypospadias repair is beneficial in decreasing complication rates.